(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present investigation was intended to compare the adolescent male and female students on depression. Multistage random sampling technique was used to draw the sample from five districts of Kashmir valley. The sample for the present study comprised of 500 adolescent students (250 male and 250 female) studying in various high and higher secondary schools of Kashmir. Data was collected by using Reynolds Adolescent Depression Scale-Second Edition (2002). Data was analysed by using Mean, S.D. and t-test. The results of the study revealed that adolescent male and female students differ significantly on depression.